All-optical switching based on optical fibre long period gratings modified bacteriorhodopsin - Korposh, Sergiy; James, S.; Partridge, M.; Sichka, M.; Tatam, R. (Elsevier, 2017)
All-optical switching using an optical fibre long-period gating (LPG) modified with bacteriorhodopsin (bR) is demonstrated. The switching process is based on the photo-induced RI change of bR, which in turn changes the phase matching conditions of the mode coupling by the LPG, leading to modulation of the propagating light. The effect was studied with an LPG immersed into a bR solution and with LPGs coated with the bR films, deposited onto the LPGs using the layer-by-layer electrostatic self-assembly (LbL) method. The dependence of the all-optical switching efficiency upon the concentration of the bR solution and on the grating period of the LPG was also studied. In addition, an in-fibre Mach-Zehnder interferometer (MZI) composed of a cascaded LPG pair separated by 30 mm and modified with bR was used to enhance the wavelength range of all-optical switching. The switching wavelength is determined by the grating period of the LPG. Switching efficiencies of 16% and 35% were observed when an LPG and an MZI were immersed into bR solutions, respectively. The switching time for devices coated with bRfilms was within 1 s, 10 times faster than that observed for devices immersed into bR solution.